AB0736 The Bepas Cohort: A Real-Life Multicenter Prospective Cohort of Psoriatic Arthritis in Belgium: Demographics and Baseline Characteristics. (15th July 2016) - De Vlam, K.; Lories, R.; Steinfeld, S.; Van Den Bosch, F.; Nzeusseu Toukap, A.; Malaise, M.; Taelman, V.; Van Bruwaene, F.; Van Den Berghe, M.; Lenaerts, J.; Joos, R.; Geusens, P.; et al.
Abstract : Background: Psoriatic arthritis (PsA) is a common form of chronic arthritis with major impact on the physical and psychosocial integrity of the patient. BEPAS (Belgian Epidemiological Psoriatic Arthritis Study) is a large prospective multicenter cohort set up in 17 Belgian rheumatology practices based in secondary and tertiary referral centers (private practice, non-academic and academic hospitals). Objectives: (1) To generate a comprehensive database to characterize the clinical presentation and the frequency of the distinct PsA subtypes; (2) to estimate the severity of disease based on disease activity scores and structural damage; (3) to estimate the impact in terms of health-related quality of life of PsA in Belgium and (4) to evaluate progression of structural damage and loss of function in patients with PsA over time. Methods: Patients with an existing or a new clinical diagnosis of PsA and fulfilling the CASPAR classification criteria were recruited. All patients gave informed consent. In the prospective study, patients are followed every year during the first 2 years with a possible extension for an additional 5 years. Demographics, clinical parameters, and data about QoL and disability were collected. X-rays of hands and feet are performed every year and axial X-rays every 2 years. Results: 461 patients (mean age: 52.79 years (±12.29), male 57%) were recruited from December 2012 to July 2014. N = number of patients with data available. Conclusions: This large cohort paints a real-life heterogeneous presentation of PsA in academic and non-academic centers in Belgium and contrast with other cohorts which are mainly academic cohorts. Further data collection will facilitate clinical and outcome studies iabout the impact and natural history of PsA in Belgium. Disclosure of Interest: K. De Vlam Grant/research support from: MSD Belgium, R. Lories Grant/research support from: MSD Belgium, S. Steinfeld Grant/research support from: MSD Belgium, F. Van Den Bosch Grant/research support from: MSD Belgium, A. Nzeusseu Toukap Grant/research support from: MSD Belgium, M. Malaise Grant/research support from: MSD Belgium, V. Taelman Grant/research support from: MSD Belgium, F. Van Bruwaene Grant/research support from: MSD Belgium, M. Van Den Berghe Grant/research support from: MSD Belgium, J. Lenaerts Grant/research support from: MSD Belgium, R. Joos Grant/research support from: MSD Belgium, P. Geusens Grant/research support from: MSD Belgium, S. Dall'Armellina Grant/research support from: MSD Belgium, I. Peene Grant/research support from: MSD Belgium, G. De Brabanter Grant/research support from: MSD Belgium, M. Van Den Berghe Grant/research support from: MSD Belgium, J. QU Grant/research support from: MSD Belgium, M. Maertens Grant/research support from: MSD Belgium, H. Leroi Employee of: MSD Belgium